2017
DOI: 10.7755/fb.115.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive dynamics of Gulf menhaden (Brevoortia patronus) in the northern Gulf of Mexico: effects on stock assessments

Abstract: Abstract-Gulf menhaden (Brevoortia patronus) produce one of the largest U.S. fisheries, yet information on reproductive dynamics of the stock is sparse. Males and females reach 50% maturity at 140.8 and 137.2 mm fork length, respectively and re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 4 publications
(7 reference statements)
4
30
0
Order By: Relevance
“…The observations of negative growth for some years could be an artifact of sampling because the same individuals are not being sampled month after month within the same year. In addition, the protracted spawning seasons for both species (Brown‐Peterson, Leaf, Schueller, & Andres, ; Lewis, Ahrenholz, & Epperly, ) could also result in negative growth for some years because harvesting individuals that were spawned at the beginning of the reproductive season could yield larger individuals than harvesting individuals that were spawned later in the season. In the Atlantic, an alternative explanation is that age‐specific migration may introduce smaller individuals into the fishery area as individuals from the southern edge of the range migrate north in the fall (Liljestrand, Wilberg, & Schueller, ).…”
Section: Discussionmentioning
confidence: 99%
“…The observations of negative growth for some years could be an artifact of sampling because the same individuals are not being sampled month after month within the same year. In addition, the protracted spawning seasons for both species (Brown‐Peterson, Leaf, Schueller, & Andres, ; Lewis, Ahrenholz, & Epperly, ) could also result in negative growth for some years because harvesting individuals that were spawned at the beginning of the reproductive season could yield larger individuals than harvesting individuals that were spawned later in the season. In the Atlantic, an alternative explanation is that age‐specific migration may introduce smaller individuals into the fishery area as individuals from the southern edge of the range migrate north in the fall (Liljestrand, Wilberg, & Schueller, ).…”
Section: Discussionmentioning
confidence: 99%
“…), individuals with these early gamete developmental stages are in the early developing subphase and are considered reproductively inactive (Brown‐Peterson et al. ). We considered Red Drum to be sexually mature when they entered the developing phase, with primary vitellogenic oocytes present in females (following the definition of Wilson and Nieland ) and secondary spermatocytes present in males.…”
Section: Methodsmentioning
confidence: 99%
“…), and stock assessments are sensitive to changes in the maturity schedule (Brown‐Peterson et al. ). Previous studies have addressed the reproductive characteristics of Red Drum in the northern GOM (Overstreet ; Fitzhugh et al.…”
mentioning
confidence: 99%
“…Ganias et al (2017) found cessation of SG recruitment and lack of massive atresia in late-season spawners in Atlantic horse mackerel, Trachurus trachurus. A similar pattern has been suggested in the clupeid Gulf menhaden, Brevoortia patronus by Brown-Peterson et al (2017).…”
Section: Box 2 -Fecundity Type Estimationsupporting
confidence: 83%
“…Mopping-up will only recover a portion of the energy that was invested in oocytes, representing a potentially expensive inefficiency. Some species, such as the Atlantic horse mackerel (Ganias et al 2017) and the Gulf menhaden (Brown-Peterson et al 2017) modulate or avoid mopping-up through a cessation of SG recruitment well before the end of spawning. In contrast, Blueback herring in the Connecticut River, even though they continue to recruit SG oocytes throughout the spawning period, avoid massive atresia by reducing the intensity of SG recruitment as spawning progresses.…”
Section: Discussionmentioning
confidence: 99%